Deconstructing the closet: A sociological reading of Tendai Huchu's novel, The Hairdresser of Harare. Issue 3 (2nd July 2016) - Ncube, Gibson
ABSTRACT: In Zimbabwe, minority sexualities remain largely concealed or closeted due to the combined effect of religious fervour, homophobia and conservative traditional beliefs. Through a close reading of Tendai Huchu's novel, The hairdresser of Harare (2010), which portrays a gay protagonist grappling with his sexual identity in modern-day Harare, this article analyses how various ways of construing homosexuality shape the self-understanding of the culture as a whole. The representation of the closet in this novel allows for a detailed examination of more than just identity concerns but also various other underlying phenomena such as the effects of power (social, economic and political), culture and religion. Bringing into conversation Goffman's (1963) theoretical work on stigma, Sedgwick's (1990) postulations on the closet as well as Foucault's (1980) critique of power and surveillance over sex and sexuality, the article argues that the fear of stigmatisation makes it difficult for Huchu's protagonist to come out of the closet. In its writing against the closet, the novel destabilises the political economy of identities and genders which places great importance on upholding heteronormative perceptions of gender and sexual orientation. The article concludes by showing the contribution such a sociological reading of the closet allows for a better appreciation of the multifaceted social and symbolic processes that may shape the construction of homosexuality in homophobic contexts such as Zimbabwe.